2022
DOI: 10.3390/children9020291
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Inflammation and Metabolic Biomarkers Are Associated with Body Composition Measures in Lean, Overweight, and Obese Children and Adolescents

Abstract: The aim of this study was to examine the associations between multiple indices of stress, inflammation and metabolism vs. body composition parameters in 121 (43 boys, 78 girls) children and adolescents, aged 5–15 y. Subjects were divided into two groups: normal weight (N) (N = 40, BMI z-score = −0.1923 ± 0.6), and overweight/obese (OB) (N = 81, BMI z-score = 2.1947 ± 1.4). All subjects completed the State-Trait Anxiety Inventory for Children (STAIC) and Children’s Depression Inventory, and underwent cortisol m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
(69 reference statements)
0
8
0
1
Order By: Relevance
“…In summary, on the basis of the same METS-IR, dyslipidemia may be a potential mechanism for lower BMI individuals to have higher levels of serum ferritin. In addition, previous studies have shown a significant positive association between fat percentage and serum ferritin levels ( 26 ), and the strength of the evidence for assessing fat percentage using BMI alone may remain limited, particularly as individuals with a higher proportion of visceral fat are more likely to develop insulin resistance, and the use of BMI in this assessment is even more limited ( 27 ). In conclusion, non-obese female participants should also be assessed regularly for changes in METS-IR, particularly if METS-IR exceeds 35.84, with caution.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, on the basis of the same METS-IR, dyslipidemia may be a potential mechanism for lower BMI individuals to have higher levels of serum ferritin. In addition, previous studies have shown a significant positive association between fat percentage and serum ferritin levels ( 26 ), and the strength of the evidence for assessing fat percentage using BMI alone may remain limited, particularly as individuals with a higher proportion of visceral fat are more likely to develop insulin resistance, and the use of BMI in this assessment is even more limited ( 27 ). In conclusion, non-obese female participants should also be assessed regularly for changes in METS-IR, particularly if METS-IR exceeds 35.84, with caution.…”
Section: Discussionmentioning
confidence: 99%
“…This correlation was not detected in the OB group, where hair and total diurnal salivary cortisol are normally elevated, implicating different factors in the activation of the HPA axis that has been observed in childhood and adolescent obesity [ 30 ]. Excessive body weight in children was associated with elevated hair and salivary cortisol in previous studies [ 31 ]. This association may be interfering with a possible association of FGF21 with cortisol.…”
Section: Discussionmentioning
confidence: 89%
“…The specimen was shaken for 2 minutes to ensure proper mixing of the extract. Once the extraction process was completed, the determination of BCC (blood cortisol concentration) and HCC (hair cortisol concentration) was carried out using an automated Electrochemiluminescence immunoassay (ECLIA) method [43].…”
Section: Hair and Plasma Cortisol Concentrationmentioning
confidence: 99%
“…The mean level of worker-occupation t (WOF, CF, NSF and DAF) of the 156 participants was 44. 43 45, 91.19] respectively. By comparing the levels of hair and plasma cortisol concentration in different demography and occupational characteristics, it was found that there were statistical differences in plasma cortisol concentrations between different sex (p < 0.05), while there were no statistical differences in hair and plasma cortisol levels between different ages, working years, education, events, occupational categories, job title, night shift, working years, working hours per week and monthly income (p > 0.05).…”
Section: Description Of the Study Populationmentioning
confidence: 99%